Comparative analysis of customer satisfaction between Siemens Elevators and competitors in the market - Badhon, Nazmus Sakib (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.